Andrija Štampar: my role model and professor - Dragoljub Kocić (Studia Lexicographica, 2023)
The aim of this presentation is to provide a personal perspective from the author, a medical professional, and his interactions with Andrija Štampar, as a professor and dean of the School of Medicine. It offers a comparison of public health based on Štampar’s principles, which the author himself followed throughout his career, and what remains of Štampar’s vision of public health in the modern era. In reference to the COVID-19 pandemic, which was mitigated in part by Štampar’s methodology, the paper emphasises Štampar’s idea that the pathology of the population should dictate the organisation of healthcare in the state. It also recalls the author’s student days and Štampar’s lectures on epidemics and hygiene. The paper highlights that Štampar raised questions about the need for medical privatisation, or ‘profiting from people’s illnesses,’ in his lectures. In line with this, the author focuses on the increasing trend of privatisation in medicine and raises questions about whether this compromises the principles of public health and ‘national’ healthcare facilities. It also addresses the issue of whether the state or health insurance institutions should be responsible for the people’s health, pointing out that, today, contracted general practitioners are primarily concerned with their own livelihoods and the job security of their medical assistants before considering their registered patients. This situation has left both doctors and their patients dissatisfied and has resulted in the dehumanisation and depersonalisation of the doctor-patient relationship, ultimately leading to a significant brain drain of young medical professionals from Croatia, while patients are ‘forced’ to turn to private healthcare institutions. Although the Government of the Republic of Croatia has declared the end of the COVID-19 epidemic, the author believes that the real epidemic in Croatia is the increase in non-communicable diseases and the fact that Croatia ranks second in the European Union according to the number of malignant diseases. The author suggests that the organisation of and access to healthcare need to be different from the current system. He believes that if Štampar were faced with such a challenge, he would advocate for the establishment of institutions similar to dispensaries or cancer centres, where patients would receive all the necessary support, examinations, and therapy.